Fluorescence and Light Scatter Calibration Allow Comparisons of Small Particle Data in Standard Units across Different Flow Cytometry Platforms and Detector Settings. Issue 6 (1st June 2020) - Welsh, Joshua A.; Jones, Jennifer C.; Tang, Vera A.
Abstract: Flow cytometers have been utilized for the analysis of submicron‐sized particles since the late 1970s. Initially, virus analyses preceded extracellular vesicle (EV), which began in the 1990s. Despite decades of documented use, the lack of standardization in data reporting has resulted in a growing body of literature that cannot be easily interpreted, validated, or reproduced. This has made it difficult for objective assessments of both assays and instruments, in‐turn leading to significant hindrances in scientific progress, specifically in the study of EVs, where the phenotypic analysis of these submicron‐sized vesicles is becoming common‐place in every biomedical field. Methods for fluorescence and light scatter standardization are well established and the reagents to perform these analyses are commercially available. However, fluorescence and light scatter calibration are not widely adopted by the small particle community as methods to standardize flow cytometry (FCM) data. In this proof‐of‐concept study carried out as a resource for use at the CYTO2019 workshop, we demonstrate for the first‐time simultaneous fluorescence and light scatter calibration of small particle data to show the ease and feasibility of this method for standardized FCM data reporting. This data was acquired using standard configuration commercial flow cytometers, with commercially available materials, published methods, and freely available software tools. We show that application of light scatter, fluorescence, and concentration calibration can result in highly concordant data between FCM platforms independent of instrument collection angle, gain/voltage settings, and flow rate; thus, providing a means of cross comparison in standard units. © 2020 International Society for Advancement of Cytometry